An experimental study of consumption orientations, environmental sustainability advertising and home-sharing adoption intentions. Issue 12 (16th August 2019) - Liu, Yu-Lun; Yuen, Tsunwai Wesley; Jiang, Han-Ling
Abstract : Purpose: Even with the evidence that participation in home-sharing is highly ecologically sustainable, the existing consumer communication studies in the hospitality sector have predominantly focussed on the social and economic benefits. This study aims to examine how the environmental sustainability benefits of home-sharing services can be effectively communicated to consumers. Design/methodology/approach: Two scenario-based experiments (Study 1: n =  377 and Study 2: n =  290) examined the effects of consumers' consumption orientations, and the appeal of environmental sustainability benefits emphasised advertising on their home-sharing adoption intentions. Findings: Study 1 demonstrated that when consumers with either a hedonic or utilitarian consumption orientation book travel accommodation, their home-sharing adoption intentions increase depending on whether advertisements are designed as hard- or soft-sell appeal, respectively. Study 2 showed that the influence of an environmental sustainability benefits emphasised advertisement that has considered consumers' consumption orientation and applied the corresponding advertising appeal design is as effective as a home-sharing service that offers economic benefits and is even better than an advertisement that emphasises social benefits, particularly for utilitarian-oriented consumers. Originality/value: This study is the first in the lodging sector examining the ways in which the environmental sustainability benefits of home-sharing services can be effectively communicated to consumers. The findings shed light on corporate practices pertaining to information that home-sharing service marketers can control and provide an essential basis for further advertising, consumer differences, environmental sustainability awareness and collaborative consumption studies.